2019
DOI: 10.3389/fenrg.2019.00041
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Energy Market Platforms Potential in Microgrids: Scenario Analysis Based on a Double-Sided Auction

Abstract: Local energy markets represent a mean for distributed energy resources trading for prosumers and energy management for utilities. In these markets, prosumers either trade or shift their loads to maximize their trading gains via communicating with an energy market platform. The utility considers the trading process as an approach to maximize the autonomy and minimize the peak loads. The benefits of the prosumer and utility can vary depending on several parameters such as the market rules, microgrid configuratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…It uses a uniform-price double-sided auction (UDA) mechanism to produce market settlement at discrete time intervals. Auction-based approaches are predominant in LEM mechanism design [4,[12][13][14], but the expected socio-economic impacts of operating consumer-facing energy infrastructure via auction on local communities has not been well-studied. On the other hand, current retail energy markets generally provide full and equal access to the energy demand of connected utility customers, but often produce conditions of energy poverty among low-income households.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It uses a uniform-price double-sided auction (UDA) mechanism to produce market settlement at discrete time intervals. Auction-based approaches are predominant in LEM mechanism design [4,[12][13][14], but the expected socio-economic impacts of operating consumer-facing energy infrastructure via auction on local communities has not been well-studied. On the other hand, current retail energy markets generally provide full and equal access to the energy demand of connected utility customers, but often produce conditions of energy poverty among low-income households.…”
Section: Methodsmentioning
confidence: 99%
“…Note that the function Ind[x] evaluates some input x as a Boolean expression; when x = true, Ind[x] = 1; when x = f alse, Ind[x] = 0. Technical market efficiency is measured by Equations ( 11) or (12), depending on the local-level supply-demand ratio. When supply is less than demand (i.e., SDR < 1), a technically efficient market allocates all supply locally; when supply at least equals demand (i.e., SDR ≥ 1), all local demand should be satisfied by local supply.…”
Section: Metric Name Metric Calculationmentioning
confidence: 99%
“…A full peer-to-peer, a community-based, and a hybrid peer-to-peer market were analyzed and compared in terms of welfare, total import costs and export revenues to the superordinate grid as well as energy exchange within the market. El-Baz et al [10] identified the major factors influencing the market outcome and energy exchange. Several aspects of market design, microgrid configurations and user behavior were investigated for selected scenarios.…”
Section: Evaluation Of Local Energy Marketsmentioning
confidence: 99%
“…Thus, the regional microgrid can effectively manage the internal distributed energy, and protect the interests of the system (Liu et al, 2020). Recent studies about local energy markets mainly includes multiagent-based (Jadhav et al, 2019), game theorybased (Anoh et al, 2020), auction theory-based (El-Baz et al, 2019;Esfahani et al, 2019) methods, and semi-market-based method under supervision (Park et al, 2016). Although the above research provides a reference for building a local energy market, there are still many limitations.…”
Section: Introductionmentioning
confidence: 99%